2014
DOI: 10.3389/fpsyt.2014.00080
|View full text |Cite
|
Sign up to set email alerts
|

Anxiety Disorders are Associated with Reduced Heart Rate Variability: A Meta-Analysis

Abstract: Background: Anxiety disorders increase risk of future cardiovascular disease (CVD) and mortality, even after controlling for confounds including smoking, lifestyle, and socioeconomic status, and irrespective of a history of medical disorders. While impaired vagal function, indicated by reductions in heart rate variability (HRV), may be one mechanism linking anxiety disorders to CVD, prior studies have reported inconsistent findings highlighting the need for meta-analysis.Method: Studies comparing resting-state… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

30
596
10
19

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 776 publications
(655 citation statements)
references
References 108 publications
30
596
10
19
Order By: Relevance
“…Similarly, studies have described decreased HRV in GAD (Thayer et al, 1996), social anxiety (Alvares et al, 2013), and specific phobia (Bornas et al, 2006). A recent meta-analysis concluded that all these anxiety disorders are all associated with reduced HRV (Chalmers et al, 2014). Taken together, the heightened sympathetic tone and reduction in parasympathetic activity, as well as the likely dysregulation of the HPA axis in anxiety disorders could lead to increased inflammation (Table 2) via similar pathways to those discussed above in the context of PTSD.…”
Section: Mechanisms Of Increased Inflammation In Fearand Anxiety-basementioning
confidence: 79%
“…Similarly, studies have described decreased HRV in GAD (Thayer et al, 1996), social anxiety (Alvares et al, 2013), and specific phobia (Bornas et al, 2006). A recent meta-analysis concluded that all these anxiety disorders are all associated with reduced HRV (Chalmers et al, 2014). Taken together, the heightened sympathetic tone and reduction in parasympathetic activity, as well as the likely dysregulation of the HPA axis in anxiety disorders could lead to increased inflammation (Table 2) via similar pathways to those discussed above in the context of PTSD.…”
Section: Mechanisms Of Increased Inflammation In Fearand Anxiety-basementioning
confidence: 79%
“…Exclusion criteria included a history or current diagnosis of any anxiety disorder and/or major depressive disorder and cardiovascular disease (hypertension, coronary artery disease, and arrhythmias) as these conditions are known to involve ANS dysfunction (Chalmers et al, 2014;Haensel et al, 2008;Kemp et al, 2012;Marano et al, 2009;Miu et al, 2009). Participants were excluded if they had a history of practicing mindfulness meditation or even minimal exposure to the practice (N60 min).…”
Section: Participantsmentioning
confidence: 99%
“…Corresponding result was also found in our laboratory design study, using simulated public speech as stressful condition. Most studies associate high anxiety with reduced HRV and increased HR, which can also be seen in anxiety disorders studies [23]. On the other hand, close similarities between allergy and anxiety were documented [8,19,20].…”
Section: Subjective Stress Differencesmentioning
confidence: 83%
“…This is even more apparent in anxiety disorders [23] and major depressive disorder [24,25]. Therefore, there are strong discrepancies between HRV findings in highly anxious and allergic people, although important links between both groups were described.…”
mentioning
confidence: 98%